Estudos em ontologias do desenvolvimento - CASTRO, Pedro Neves de (Universidade Federal do Pará, 2025)
This work seeks to understand the transformation in the interpretation of the Brazilian nation and the State between the 1920s and the 1950s. The transition from an anti-regionalist conception to a perspective centered on national developmentalism marks a crucial turning point in this period. The central aim is to comprehend the processes and circumstances that gave rise to this shift by analyzing the ontologies of development in the formation of the Brazilian republican State. Composed of two chapters, the study explores the ontologies of the ideas of Brazil, the State, and development, seeking to foster dialogue rather than provide definitive answers, thereby encouraging multidisciplinary reflection on political and economic thought. In the first chapter, titled "Ontologies of the State and the Idea of Development," the philosophical roots of ontology are examined alongside the phenomenological context and variables that influenced the construction of thought models responsible for reflections on the "being" of the State and its crucial role in shaping the ideas of development. The second chapter, "Ontologies of Brazilian Political and Social Thought," presents an overview of different perspectives on Brazil as a managing State and productive space. By discussing developmentalism in the Brazilian context, the study explores the emergence of the concept and the influence of economic and social debates preceding the 1950s, a period when the economic school of thought and developmentalism were consolidated. This work introduces ontological analysis into the understanding of development, emphasizing the hermeneutic and interpretative approach adopted to examine the sources that contributed to the social construction of the concept of development and its state-driven practice.